Spesies Semut yang Ditemukan di Sekitar Perkebunan Kelapa di Daerah Banyuasin Sumatera Selatan Indonesia - Anggraini, Erise; Riyanti, Tia Ellisa; Sinaga, Tessia Masnita; Simbiring, Riki Suranta; Sefrila, Marlin; Kurnianingsih, Astuti; Ikhsan, Zahlul (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Anggraini, E., Riyanti, T. E., Sinaga, T. M., Simbiring, R. S., Sefrila, M., Kurnianingsih, A., Ikhsan, Z. 2023. Ant species found around coconut plantations in the Banyuasin Region of South Sumatra Indonesia. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 749-755). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The coconut plant (Cocos nucifera L.) is one of the agricultural commodities that is widely cultivated in almost all regions of Indonesia, especially in the Banyuasin Regency, South Sumatra, Indonesia. Weeds are found around coconut plantations. Ants are known as predators of insect pests and are found in weed habitats. This research aimed to determine the types of ant species that dominate coconut plantations in the Banyuasin, South Sumatra, Indonesia. Data was collected by field observation using the plant survey method. The survey was carried out through direct observation of the farmer coconut plantations covering an area of 4 hectares. Observations were done by observing the ant species found around the coconut plants. Ants species found on coconut plantations in the Banyuasin Regency were Dolichoderus sp., Oecophylla smaragdina, and Polyrhachis bicolor. The most dominant ant found in coconut plantations in the Banyuasin was O. smaragdina with a total of 742 individuals. The fewest ants found was P. bicolor with a total of 578 individuals.